In vivo adaptive antimicrobial resistance in Klebsiella pneumoniae during antibiotic therapy - Li, Shuangshuang; Feng, Xudong; Li, Min; Shen, Zhen (Frontiers in Microbiology, 2023)
Klebsiella pneumoniae is one of the leading pathogens contributing to antimicrobial resistance. The emergence of carbapenem-resistant K. pneumoniae (CRKP) has put the use of clinical antimicrobial agents in a dilemma. In particular, CRKP exhibiting resistance to ceftazidime/avibactam, tigecycline and colistin have raised great clinical concern, as these are the last-resort antibiotics for the treatment of CRKP infections. Within-host evolution is a survival strategy closely related to the emergence of antimicrobial resistance, while little attention has been paid to the in vivo genetic process of conversion from antibiotic-susceptible to resistant K. pneumoniae. Here we have a literature review regarding the in vivo evolution of resistance to carbapenems, ceftazidime/avibactam, tigecycline, and colistin in K. pneumoniae during antibacterial therapy, and summarized the detailed resistance mechanisms. In general, acquiring blaKPC and blaNDM harboring-plasmid, specific mutations in blaKPC, and porin genes, such as ompK35 and ompK36, upregulation of blaKPC, contribute to the development of carbapenem and ceftazidime/avibactam resistance in vivo. Overexpression of efflux pumps, acquiring plasmid-carrying tet(A) variants, and ribosomal protein change can lead to the adaptive evolution of tigecycline resistance. Specific mutations in chromosomes result in the cationic substitution of the phosphate groups of lipid A, thus contributing to colistin resistance. The resistant plasmid might be acquired from the co-infecting or co-colonizing strains, and the internal environment and antibiotic selection pressure contribute to the emergence of resistant mutants. The internal environment within the human host could serve as an important source of resistant K. pneumoniae strains.